Possible involvement of proteinaceous and non-proteinaceous trehalase inhibitors in the regulation of hemolymph trehalose concentration in Bombyx mori - Nujira Tatun (2018)
The midgut of the silkworm Bombyx mori contains two types of trehalase: soluble and membrane-bound. The trehalose concentration in larval hemolymph remains substantially high through the feeding period of the last (fifth) larval instar, despite appreciable trehalase activity through this period. We found that B. mori larval hemolymph contains two types of trehalase inhibitor, a proteinaceous inhibitor (inhibitor-P) and an inhibitor that is extractable with methanol and ethanol (inhibitor-M). Both inhibit the two types of trehalase, but with different sensitivities. Inhibitor-P inhibited soluble trehalase (ST) more effectively than membrane-bound trehalase (MT), while inhibitor-M inhibited MT slightly more than ST. The inhibitory activity of inhibitor-M was high during the early to middle feeding period, followed by a sudden decrease during the late feeding period. Inhibitor-P activity increased throughout the feeding period, and markedly decreased 2 days after gut purge. Thus, the two inhibitors exhibited stage-specific changes in the hemolymph, indicating coordinated inhibitory activity. Therefore, trehalose concentration regulation in the hemolymph appears to be complex, consisting of at least two inhibitors and two types of trehalase.